New Industries from New Places : the Emergence of the Hardware and Software Industries in China and India. - Gregory, Neil (World Bank e-Library., 2009)
Software comes from India, hardware comes from China. Why is that? Why did China and India take such different paths to global dominance in new high-tech industries? Will their paths continue to diverge or converge? How can other countries learn from their successes and failures in reaching global scale in new industries? To answer these questions, this book presents the first rigorous comparison of the growth of the IT industries in China and India, based on interviews with over 300 companies. It explains the different growth paths of the software and hardware sectors in each country, providi.